Obesity dysregulates the pulmonary antiviral immune response - Mark Almond; Hugo A. Farne; Millie M. Jackson; Akhilesh Jha; Orestis Katsoulis; Oliver Pitts; Tanushree Tunstall; Eteri Regis; Jake Dunning; Adam J. Byrne; Patrick Mallia; Onn Min Kon; et al. (Nature Communications, 2023)
Abstract Obesity is a well-recognized risk factor for severe influenza infections but the mechanisms underlying susceptibility are poorly understood. Here, we identify that obese individuals have deficient pulmonary antiviral immune responses in bronchoalveolar lavage cells but not in bronchial epithelial cells or peripheral blood dendritic cells. We show that the obese human airway metabolome is perturbed with associated increases in the airway concentrations of the adipokine leptin which correlated negatively with the magnitude of ex vivo antiviral responses. Exogenous pulmonary leptin administration in mice directly impaired antiviral type I interferon responses in vivo and ex vivo in cultured airway macrophages. Obese individuals hospitalised with influenza showed dysregulated upper airway immune responses. These studies provide insight into mechanisms driving propensity to severe influenza infections in obesity and raise the potential for development of leptin manipulation or interferon administration as novel strategies for conferring protection from severe infections in obese higher risk individuals.